Effects of heat waves on human mortality, Galicia, Spain - DeCastro, M. (2011)
Two major heat waves were identified in Galicia over the period 1987–2006. The first was detected in July 1990, and the second in August 2003. The most likely factor contributing to both heat waves was the north-eastward displacement of the Atlantic subtropical high. The effect of these heat waves on excessive mortality was assessed through the analysis of temperature means and normalized mortality exceedance of the 95th percentile of maximum temperature and mortality. The study was disaggregated by province, gender and age, but only the population segment older than 65 yr was targeted. In terms of temperature exceedance, the 2003 heat wave was slightly more intense than the one in 1990. However, the resulting mortalities were much higher in 1990; this difference is possibly due to improvements in welfare that occurred in the interim period. For both heat waves, effects were more severe in women than in men.